A method for threshold voltage extraction in junctionless MOSFETs using the derivative of transconductance-to-current ratio. (June 2020) - Rudenko, T.; Nazarov, A.; Barraud, S.; Kilchytska, V.; Flandre, D.
Highlights: gm /ID -derivative method for threshold voltage extraction in junctionless MOSFETs. Method validation with analytical theory, numerical simulations and experiment. Higher accuracy and reliability compared to the tranconductance derivative method. Abstract: In this paper, using numerical simulations, analytical modeling and experimental data, we validate the applicability of the transconductance-to-current ratio ( gm / ID ) derivative ( d ( gm / ID )/ dVG ) method for extracting the threshold voltage ( VTH ) in junctionless (JL) MOSFETs and show its advantages over the commonly-used transconductance derivative (or double derivative of drain current) method ( dgm / dVG ≡d 2 ID / dVG 2 ). It is shown that, although both methods are based on the same theoretical VTH -criterion, the d ( gm / ID )/ dVG method is more accurate than the d 2 ID / dVG 2 method due to its lesser sensitivity to the gate-voltage-dependent mobility and series resistance parasitic effects, being particularly important in JL MOSFETs.